Wake-up time and academic performance of university students in Indonesia: A cross-sectional study - Sofyana, Meida; Wibowo, Rakhmat Ari; Agustiningsih, Denny (Frontiers in Education, 2022)
Several studies have highlighted the link between sleep, learning, and memory. Strong evidence shows that sleep deprivation can affect a student’s ability to learn and academic performance. While delayed sleep-wake phase disorder was prevalent among young adults, available evidence showed an inconclusive association between sleep times and academic performance in university students. Therefore, we conducted a cross-sectional study among university students in Indonesia to collect their sleep duration, bedtime, wake-up time, and academic performance. An analysis of 588 university students in Indonesia found that only 38.6% of students sufficiently slept, and their median bedtime and wake-up time was 11:30 pm and 5:30 am, respectively. Gender and wake-up time accounted for a 5.8% variation in academic performance (adjusted R2=4.5%) after controlling for sleep duration, bedtime, body mass index, the field of study, batch year, and physical activity. Male had 0.116 (95% Confidence Interval (CI) -.167 to -.064) lower grade point average (p<0.001) than female and students who wake up later had 0.077 (95% Confidence Interval .025 to .129) greater grade point average (p=0.004) than students who wake-up earlier. The prevalence of sleep deprivation related to the delayed sleep-wake phase among university students in Indonesia was high. Since wake-up time was related to the increased grade point average, the university should consider developing sleep-friendly policies and interventions to improve their academic performance.